(untitled) (Anclajes, 2021)
This article offers an approach to the journal Cursos y Conferencias (Buenos Aires, 1931-1960), published by the Colegio Libre de Estudios Superiores (1930-1970). In the 1940s, under Arturo Frondizi’s direction (1941-1952), the journal underwent a series of changes that redirected its course. Following recent developments in the study of periodical publications, this article proposes a reading on the syntax of the journal, approaching it as an autonomous object. The analysis reveals that a series of editorial decisions made during this period spurred a change in the journal’s profile: from functioning as an organ of institutional diffusion, it became an autonomous cultural project and a space for active intervention in Argentina’s public life.